C-reactive protein and procalcitonin as markers of mortality in hemodialysis patients: a 2-year prospective study - Chauveau, Philippe; Level, Claude; Lasseur, Catherine; Bonarek, Hervé; Peuchant, Evelyne; Montaudon, Danièle; Vendrely, Benoît; Combe, Christian (Journal of renal nutrition, 2003)
We have previously shown in a transversal study that PCT combined to CRP is associated to an altered nutritional status in hemodialysis patients. In a 2-year prospective study, we have assessed the relationship between markers of inflammation or nutrition and mortality. Two-year prospective study, in 61 patients dialyzed in our unit (29 M/32 F, age 63 +/- 15 years, on dialysis for 76 +/- 94 months, 12 hrs/wk, on high-flux (HF) membrane for 25 patients and low-flux (LF) for 36 patients, without reuse). Kt/V was 1.53 +/- 0.30. Hospital-based dialysis unit. CRP, PCT, ferritin, albumin, and prealbumin, were measured in 04/99 (T0) and every 6 months thereafter. Interleukin-6 (IL6) and fibrinogen were measured at the start of study. The outcome and the causes of death of patients were noted in 58 patients, 3 patients were lost of follow-up. The mortality (24 deaths) was 42% at 2 years in this hospital based unit. The main causes of mortality were cardiovascular diseases (71%) and infection (17%). Patients were classified according to their CRP (CRP+ if CRP > or = 5 mg/L; n = 40), and PCT values (PCT + if PCT > or = 0.5 ng/mL; n = 25). IL6 level was > or = 10 pg/mL for 95% of the patients. Mortality was higher in the CRP+ group (Kaplan-Meier test P < .01) but not in the PCT or IL6 positive patients. All patients of the CRP+ group at T0 remained CRP+. Only 56% of patients of PCT+ remained positive at 6 months. When patients were grouped according to CRP quartile the difference on survival remained significant (P = .03), patients who were classified in the third and fourth quartile (upper than 9.9 mg/L), exhibited a higher rate of mortality than the lower quartile. The concomitant presence of a high level of PCT and CRP was associated with a worsened nutritional status at T0 but PCT level had no influence on 2-year mortality. In this 2-year prospective study in a hospital-based cohort of high-risk hemodialysis patients, elevated CRP, but not raised PCT, was associated with increased mortality. Inflammation remained present throughout a 2-year follow-up in patients with an initial CRP higher than 5 mg/L. An upper value of CRP above 9.9 mg/L is independly predictive of mortality, mainly from cardiovascular causes. The association of high PCT and CRP was no more predictive of mortality than high CRP.